Viscoelastic Models for Passive Arterial Wall Dynamics (Advances in Applied Mathematics and Mechanics, 2018)
This paper compares two models predicting elastic and viscoelastic propertiesof large arteries. Models compared include a Kelvin (standard linear) modeland an extended 2-term exponential linear viscoelastic model. Models were validatedagainst in-vitro data from the ovine thoracic descending aorta and the carotidartery. Measurements of blood pressure data were used as an input to predict vesselcross-sectional area. Material properties were predicted by estimating a set ofmodel parameters that minimize the difference between computed and measuredvalues of the cross-sectional area. The model comparison was carried out usinggeneralized analysis of variance type statistical tests. For the thoracic descendingaorta, results suggest that the extended 2-term exponential model does not improvethe ability to predict the observed cross-sectional area data, while for the carotidartery the extended model does statistically provide an improved fit to the data.This is in agreement with the fact that the aorta displays more complex nonlinearviscoelastic dynamics, while the stiffer carotid artery mainly displays simpler linearviscoelastic dynamics.